The Effect of Budgetary Participation, Organizational Commitment, and Locus of Control on Budgetary Slack with Information Asymmetry as a Moderating Variable - Azwaliza Aziz Izlin; Nyimas Wardatul Afiqoh (Transpublika Publisher, 2026)
Corporate budgeting serves as an operational blueprint outlining subsequent organizational activities and bridging the gap between high-level strategies and tangible short-to-long-term objectives. This study examines the deterministic effects of budgetary participation, organizational commitment, and Locus of Control (LoC) on budgetary slack, while positioning information asymmetry as a moderating variable. Employing a quantitative framework, empirical data were gathered via purposive sampling targeting managerial and accounting personnel within PT Semen Indonesia Group, East Java. Primary data collection was executed through an online Likert-scale questionnaire and subsequently evaluated utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS). The empirical findings indicate that neither budgetary participation nor organizational commitment exerts a direct influence on budgetary slack; however, their relationships are significantly amplified by information asymmetry. Conversely, locus of control demonstrates negligible direct or moderating impacts. These insights highlight the critical necessity of mitigating information asymmetry to suppress budgetary slack, thereby underscoring the urgency for transparency-driven and accountable budgeting policies. Acknowledging constraints such as a parsimonious model design and a confined sample size, this paper suggests that future inquiries incorporate multi-dimensional frameworks and broader institutional representations.